The EU-Russia Gas Relationship: a mutual dependency - Chloé Le Coq; Elena Paltseva (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
Current debate on the energy security in the EU often stresses the EU dependency on gas imports from Russia. However, Russia is no less dependent on the EU – more than half of its gas exports goes to Europe. The purpose of this paper is to characterize this mutual dependency through an index-based approach, and to discuss how the development of gas markets may affect such dependency. We suggest a unified framework to assess the security of gas supply for the EU and the security of gas demand for Russia, and construct dependency indexes for both parties. Our approach accounts not only for the traditional import/export dependency measures but also for the balance of power between Russia and the EU. The proposed methodology is then used to address the evolution of the EU-Russia gas relationship in the view of gas market's developments. New gas pipelines projects (e.g., South Stream, Nabucco) and increasing use of liquefied natural gas are all likely to impact both the demand side and the supply side of the EU-Russia gas trade, and affect mutual gas dependency between the EU and Russia.
Keywords: C81; Q40; Q48; 330; Energy Security; European Union; Gas transit risks; Index; Russia